Thinking Again And Again: The Link Between Rumination And Creativity With Anxiety As A Mediator - Escobar , Divine Grace C.; Perez, Jeannie A. (Academic Journal of Psychology and Counseling, 2023)
It is not uncommon to find that many creative people are anxious and ruminative. This study investigated the association between two types of rumination (brooding and reflection) and creativity and the mediating role of anxiety in a general population. This cross-sectional quantitative study involved 135 Filipino adults, whose ages ranged from 18 to 53 years old. The respondents were recruited online using the chain referral technique. Three instruments of measurement were used in facilitating the online data collection namely, Rumination Response Scale – Short Form, Beck Anxiety Inventory (BAI), and Runco Ideational Behavior Scale (RIBS). Mediation analyses were performed using the General Linear Model technique to test the hypotheses of the study. The results showed a positive association between the two types of rumination and creativity. Anxiety also showed a significant positive association with creativity and was a significant mediator between the two types of rumination and creativity. The findings added a new contribution to the existing body of knowledge about the mediating role of anxiety between rumination and creativity. Implications for counseling were offered where rumination and anxiety could be tapped as psychological resources to improve creativity. Future research directions were also offered.